Pandangan Islam terhadap Akuntansi Syariah - Chair, Wasilul (Shafin: Sharia Finance and Accounting Journal, 2022)
This study aims to explain accounting thinking in a sharia perspective. This research is a library research, namely the study explains the concepts, theories and accounting principles in Islamic views. Data collection techniques are carried out by reading, reviewing and recording various literature or reading material that is in accordance with the subject. The results in this study are that the Shari’ah Accounting Paradigm is accounting that emphasizes the legal aspects and ethics of Islamic business. Shari’ah accounting leaned on the source of Islamic law, namely the Qur’an, Hadith, Fiqh (Qiyas, Ijtihad and IJMA). In the Islamic Shari’at Accountants, the presentation of its report is not just a means of determining the capital and measuring profits through the discharge of capital, but also presents a report that adheres to the rules contained in the Qur’an and Hadith, And can not violate forever, in other words reporting information according to the principles of Muamalah. A very important point to be introduced is that the application of shari’ah accounting based on the shari’ah paradigm is a part related to monotheism al-ibadah.